Association of X-ray repair cross-complementing group 1 Arg399gln polymorphisms with the susceptibility to develop oral squamous cell carcinoma in tamol chewer's population in Assam, India - Lhakit Lepcha; Manash Pratim Sarma; Amal Chandra Kataki; Bala Gopalan Unni (Wolters Kluwer Medknow Publications, 2021)
Background: Various environmental factors have been reported to play key role in the development of oral squamous cell carcinoma (OSCC). A lesser known risk factor of oral cancer in India is the uncontrolled use of areca nut chewing. In North-East India, Areca nut, locally called as "Tamol" in Assam, is raw betel nut, lime and betel leaf without tobacco, which are more effective as compared to dried which can be the important contributing factor for OSCC. Objectives: The aim of the study was to detect the association between XRCC1 polymorphisms and increased risk of OSCC in tamol chewers population in Assam, India. Methods: 50 OSCC patients, 50 tamol chewers and 50 controls were enrolled in the study. XRCC1 Arg399Gln polymorphisms were determined by using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). Results: There was a significant association for XRCC1 codon 399 (Arg/Gln+Gln/Gln) (p<0.05; OR=1.909, CI= 0.8622- 4.227) with the wild type in cancer sample as compared with control sample. Similarly, the positive association for 399G/G (p<0.05; OR =2.842, CI = 0.919-8.79) genotypes with oral carcinoma and control sample. In case of tamol chewers, the AA genotype was found to be associated with 2-fold (OR- 2.25, CI= 0.709-7.14) increase risk of developing oral cancer while GA+AA genotype was associated with one and half fold (OR-1.62, CI=0.7354- 3.568) risk of developing oral cancer. Conclusions: Based on these results, the XRCC1399G>A genotype could be used as a useful molecular biomarker to predict genetic susceptibility in tamol chewers population and its susceptibility to develop OSCC.